THE MODERATING EFFECT OF THE EFFECTIVENESS OF THE AUDIT COMMITTEE BETWEEN OWNERSHIP CONCENTRATION AND INTELLECTUAL CAPITAL DISCLOSURES AMONG COMPANIES IN GULF CO-OPERATION COUNCIL - Helmi Qeshta, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the moderating impact of the effectiveness of the audit committee on the relationship between concentration of ownership and disclosure of intellectual capital (IC). Empirical data was taken from the annual reports of 119 top-noted corporations in the Gulf Cooperation Council (GCC) countries at the end of 2017 using a content review methodology. Multiple hierarchical regression is used to check for moderator influence. Our findings show that ownership concentration has an insignificant relationship with IC disclosure. However, our analysis shows that the extent of the effectiveness of the audit committee in GCC firms moderates the relationship between the concentration of ownership and the disclosure of IC. The results of the study are relevant for policymakers and investors, as they indicate that the efficacy of the audit committee in companies owned or regulated by the large shareholder would minimize the knowledge asymmetry and the agency issue by allowing management to reveal more knowledge to outside parties. Therefore, policymakers must search for other strategies that allow management to enhance the disclosure of ICs in companies with a high concentration of ownership. This research adds to the literature as it is the first research to investigate the variables that may influence the relationship between the concentration of ownership and the disclosure of IC in the GCC countries.